Rural Women’s Agency on Forest and Land Governance in The Midst of Change: Case Study in Five Provinces - Andi Misbahul Pratiwi; Abby Gina Boangmanalu (Yayasan Jurnal Perempuan, 2019)
Women in rural areas face serious problems as a result of ecological social changes in the village–which are almost mutually interconnected with the expansion of extractive industries and rural development paradigm. Forests and land become as the identity that cannot be left behind in seeing changes in rural areas. Sustainable forest and land governance are one of the ways to reduce the risk of environmental damage & degradation, land use change, deforestation, and loss of food resources and livelihoods of rural communities. One of the principles of sustainable forest and land governance is transparency and participation. In this study we found, explain, and analyse 1) how the social ecological changes in the villages through the expreinces of women who is a trailblazer or local champion in 5 provinces (West Papua, East Kalimantan, Aceh, Central Sulawesi, Bengkulu); 2) the struggle of rural women in seizing the right to information and participation in the process of forest and land governance; 3) women’s agency in creating positive socio-ecological changes in the village area. This research found that women’s agencies are not single and are produced from various forms of power, namely the power/ability to influence and reduce barriers, to change at the household and community level, the power to organize and change existing hierarchies, the power to increase individual awareness and the desire to change, the strength of collective action and solidarity.